Dampak Pendidikan Islam Non-formal terhadap Pembentukan Karakter Keagamaan Anak dan Remaja - Hana Wibowo, Adita Rizki; Darodjat, Darodjat (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
Character formation faces complex challenges in the 4.0 era, so that it can trigger a decline in spirituality and social problems. The role of formal education in overcoming it is often limited, so there is a need for the role of non-formal Islamic education as a complement. This study aims to examine in depth the impact of non-formal Islamic Education. This study uses a qualitative approach with the literature review study method. The data collection process begins with the formulation of research questions, followed by the search for relevant literature using specific keywords in national and international scientific articles. Literature selection was conducted based on quality, by adopting the criteria of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A systematic analysis of 500 articles successfully identified 432 articles that were testable, and 418 articles were included in the comprehensive analysis. The results of the study show that non-formal Islamic education has a significant multifaceted impact, including increasing religious awareness of adolescents and children, resilience, social awareness, and prevention of juvenile delinquency. The implementation of non-formal Islamic education through a hidden curriculum can enable the adaptation of children and adolescents through habituation and example in the midst of the transformation of religious behavior in the 4.0 era that faces digital turbulence. Non-formal Islamic education can fill the void that exists in formal education in the formation of the character of children and adolescents, especially through unique pedagogical mechanisms and hidden curriculum.